P683 Racial and ethnic disparities related to neisseria gonorrhoeae among U.S. military active duty service members. (14th July 2019) - Early, June; Waggoner, Sandra; Garges, Eric
Abstract : Background: Neisseria gonorrhoeae is the second most common reportable infection in the United States, which if undiagnosed and untreated, can lead to severe long-term sequelae. Active duty U.S. Military service members are risk-taking young adults; however, military service offers some inherent control for social determinants often associated with increased risk of sexually-transmitted infections. Even in the absence of disparities in income and education, increased burden of disease among racial and ethnicity minorities may still exist. Herein, we describe the association between race/ethnicity and gonorrhea among active duty service members. Methods: This study was conducted among symptomatic and high risk patients enrolled at military infectious disease clinics from 2012 to 2017. Outcome variables were based on nucleic acid amplification test results extracted from medical records. The magnitude of association was assessed using adjusted odds ratios and 95% confidence intervals. Results: Data from 488 active duty participants were analyzed. The crude prevalence of gonorrhea and chlamydia among this clinic population was 17% and 25%, respectively. After adjusting for sex and age, non-Hispanic black service members had 3.5 times greater odds (p=0.000) and Hispanic service members had 2.9 times greater odds (p=0.009) of gonorrhea compared to non-Hispanic white service members. This phenomenon was not observed when comparing odds of chlamydia among blacks or Hispanics to whites. Conclusion: Despite similarities in income and education, black and Hispanic service members still bear a disproportionate burden of gonorrhea illness. Service members of color may have unique risk factors that predispose them to gonorrhea. Findings suggest that interventions aimed at reducing gonorrhea should be targeted towards persons of color to ensure disparities in disease burden are effectively addressed. Future studies should examine sexual behaviors among black and Hispanic service members that may be contributing to increased odds of gonorrhea within the military population. Disclosure: No significant relationships.